The acylpolyamines from spider venoms - Palma, Mario Sergio [UNESP] (Elsevier, 2012)
Acylpolyamines are low molecular mass toxins occurring exclusively in the venoms from solitary wasps and some groups of spiders. Their chemical structures have been elucidated using hyphenated techniques of mass spectrometry, such as LC-MS and MS/MS, or through direct analysis with different types of NMR analyses. The chemical structures of the acylpolyamine toxins from the venoms of Nephilinae orb-web spiders appear to be organized into four parts based on the combinatorial way that the chemical building blocks are bound to each other. An aromatic moiety (part I) is connected through a linker amino acid (part II) to a polyamine chain (part III), which in turn may be connected to an optional tail (part IV). The polyamine chains were classified into seven subtypes according to the different combinations of chemical building blocks. These polyamine chains, in turn, are connected to one of three chromophore moieties: a 2,4-dihydroxyphenyl acetyl group, a 4-hydroxyindolyl acetyl group, or an indolyl acetyl group. They may be connected through an asparagine residue or sometimes through the dipeptide ornithyl asparagine. Also, nine different types of backbone tails may be attached to the polyamine chains. These toxins are noncompetitive blockers of ionotropic glutamate receptors with neuroprotective action against the neuronal death and antiepileptic effect. Thus, compounds of this class of spider venom toxin seem to represent interesting molecular models for the development of novel neuropharmaceutical drugs. © 2012 Elsevier B.V. All rights reserved.
Keywords: Glutamate receptors; Neuroblockers; Orb-web spiders; Structure determination; Toxins